Supramolecular self-assembly of oleylamide into organogels and hydrogels: a simple approach in phase selective gelation of oil spills. Issue 1 (2nd January 2020) - Eftekhari-Sis, Bagher; Bagheri, Azam; Younesi Araghi, Hessamaddin; Akbari, Ali; F. Paige, Matthew
ABSTRACT: A new gelator based of oleylamide has been introduced, which was gelled nonpolar hydrocarbon and CCl4 solvents through self-assembly. Also, the gelator formed a two-component hydrogel in combination with SDS, an anionic surfactant. UV-Vis studies revealed that the H-type and J-type aggregation of organogels in hexane and hydrogel in water, respectively. The xerogel, obtained by evaporating the solvent of organogel, selectively gelled and adsorbed oil spills on water surfaces. The effect of the various parameters, including temperature, water acidity and pH on the oil spill adsorption was studied, revealing the high ability of the xerogel to removing the oil contamination from water in up to 10 min. The novelty of this work is the ability of the xerogel to the phase selective gelation of oil without an extra auxiliary and/or heat. Simple synthesis of gelator started with oleic acid from natural resources is a main advantage of the present work.